2021
DOI: 10.1371/journal.pone.0248707
|View full text |Cite
|
Sign up to set email alerts
|

Drug-resistant TB prevalence study in 5 health institutions in Haiti

Abstract: Objectives Tuberculosis (TB) is the leading infectious cause of death in the world. Multi-drug resistant TB (MDR-TB) is a major public health problem as treatment is long, costly, and associated to poor outcomes. Here, we report epidemiological data on the prevalence of drug-resistant TB in Haiti. Methods This cross-sectional prevalence study was conducted in five health centers across Haiti. Adult, microbiologically confirmed pulmonary TB patients were included. Molecular genotyping (rpoB gene sequencing an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…Comparing these estimations with international epidemiological data, the number of DRTB-T2DM cases in Sinaloa, Mexico, was higher (16%) than in Shandong, China (5.8%) [ 19 ]. Moreover, DRTB-HIV registers were not found in Mexico, but studies in other countries have reported a prevalence of 13.6%, in Nigeria, and 28.4%, in Haiti [ 39 , 40 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Comparing these estimations with international epidemiological data, the number of DRTB-T2DM cases in Sinaloa, Mexico, was higher (16%) than in Shandong, China (5.8%) [ 19 ]. Moreover, DRTB-HIV registers were not found in Mexico, but studies in other countries have reported a prevalence of 13.6%, in Nigeria, and 28.4%, in Haiti [ 39 , 40 ].…”
Section: Discussionmentioning
confidence: 99%
“…The risk of DR-TB was found to be two times higher in HIV patients compared to those with T2DM. Recently, in a cross-sectional study in Haiti, scholars reported that DR-TB is 2.5 times more frequent in patients with HIV than in non-HIV patients [ 40 ]. Interestingly, no significant associations between T2DM and DR-TB were observed, despite previous reports having suggested a 3.1 times greater risk of TB in T2DM patients when compared to those without T2DM [ 45 ].…”
Section: Discussionmentioning
confidence: 99%